Preferensi Jenis Pohon Tempat Bersarang Orangutan (Pongo pygmaeus) di Kawasan Punggualas Taman Nasional Sebangau Kalimantan Tengah: Preference Species of Tree where Orangutans (Pongo pygmaeus) Nested in the Area of Punggualas Sebangau National Park Central Kalimantan - Simbolon, Lilis S.; Hidayat, Nisfiatul; Octavianus, Robby; Madiyawati, Milad; Surasana, I Nyoman (HUTAN TROPIKA, 2023)
The purpose of this study was to determine the level of preferences and characteristics of orangutan nesting sites in Area Punggualas Sebangau National Park, Central Kalimantan using the strip transect method, a path 1 km long and 25 m wide on each side of the right and left lanes. Nest observations were carried out on 10 transects and the distance between transects was ±200 m. Based on observations of the habitat characteristics and preferences of orangutan nest trees (Pongo pygmaeus) in Punggualas, there are 13 tree species that orangutans like, namely Sagagulang, Bintan, Galam Merah, Kajunjung, Mahalilis, Pampaning, Tatumbu, Rasak, Tutup Kabali, Forest Mangosteen, Nyatoh bawui , Uweh, and Tarantang. The physical tree parameters (total tree height, tree diameter, nest height, and nest position) show X2Hitung > X2Tabel, which means that each variable has a relationship with the frequency of finding significant nests for orangutans to be nests.